Aminoquinoline-triazine Conjugates: Design, Synthesis, Antibacterial Activity, and SAR Analysis - Ansari, Sajidul H.; Sahu, Supriya; Shakya, Anshul; Ghosh, Surajit Kumar; Singh, Udaya Pratap; Bhat, Hans Raj (Letters in Drug Design & Discovery, 2023)
Aim: Frequent use of antibiotics is responsible for the development of antibiotic resistance; thus, there is an urgent need for the development of new antibacterial agents that act by novel mechanism pathways. Objective: The aim of the study was to develop hybrid novel 4-aminoquinoline 1,3 5-triazine derivatives and determine their antibacterial activity. Methods: Novel hybrid 4-aminoquinoline 1,3,5-triazine derivatives were synthesized by nucleophilic substitution and characterized by different spectroscopic methods. Furthermore, in silico study was carried out with 16S-rRNA A-site (PDB id: 1J7T using Discovery Studio 2018 software) to exemplify key structural interactions. In vitro antibacterial activity of target compounds was evaluated against three Gram-positive and three Gram-negative bacterial strains. Results: In silico results have shown compound 8c to have both hydrophobic interactions (conventional hydrogen bond interactions with A A:16, A A:17 and carbon hydrogen bond with U A:14, G A:15) and hydrophilic interactions (G A:18G A:13, G A:15 and U A:19) along with excellent CDocker energy (- 28.2942). In vitro antibacterial results revealed that compound 8c showed better zone of inhibition against S. aureus (gram-positive) and E. coli (gram-negative) as compared to standard drug Cefixime. Conclusion: Our study demonstrated that in silico study supported the experimental study, and the developed 1,3,5-triazine-4-aminoquinoline derivatives may be used as potential leads for future antibacterial drug development.
Keywords: triazine